Predictors of successful transition to Registered Nurse. (22nd August 2012) - Phillips, Craig; Esterman, Adrian; Smith, Colleen; Kenny, Amanda
Abstract Aim To identify predictors of successful transition from undergraduate student to registered nurse and to identify whether any particular pre‐registration paid employment choice impacted on transition. Background Nursing students in Australia and internationally, engage in a variety of paid employment whilst completing their university studies. However, there is little empirical evidence about the different types of employment chosen by students and any relationship to graduate nurse transition. Design A descriptive questionnaire survey. Method This cross‐sectional study was conducted with newly graduated nurses throughout Australia. The survey data were collected over 4 months in 2011, with 392 registered nurses completing a questionnaire. Results Respondents were categorized into four groups, according to their chosen work type (hospitality/retail, enrolled nurse, other healthcare worker, and non‐worker) and transition scores were identified. Transition scores were significantly higher for undergraduates who were employed compared with non‐workers. Postregistration institutional work factors appeared to be stronger predictors of successful transition than pre‐registration employment factors. Assistance in dealing with complex patients, orientation to a new environment, and respect from colleagues were the best predictors for successful transition. Conclusions Engaging in some form of paid employment in the final year of undergraduate university study is beneficial. However, it is not pre‐registration employment choice per se that is the best predictor of successful transition, but the influence of work factors which new graduates experience in their first year of practice.